Eurasian flavors : defining cultural identity in postcolonial Singapore, 1960s–1990s - Ong, Shi Yuan (Nanyang Technological University, 2022)
Members of the Eurasian minority found themselves vulnerable to losing their identity during the post-colonial period, as Singapore’s multiracial framework ostracised them. Hence, the thesis explores how the hybridised Eurasian population negotiated their cultural identity in cosmopolitan Singapore. Previous scholarships have addressed the ambiguity surrounding Eurasian identity while also recognising the significance of food as a means for cultural expression. Eurasian cuisine represents the community since it reflects their hybridised status. Consequently, to what degree was the culinary culture a deliberate endeavour to defend and define the Eurasian identity? Some community members recognised the precarious situation, opened restaurants, wrote cookbooks, and more to showcase the multifaceted Eurasian culinary traditions. Employing Stuart Hall’s second cultural identity theory of “becoming” rather than “being,” the thesis investigates food as a microcosm of cultural expression and argues that the Eurasian cultural identity cannot be defined by a fixed set of cultural values but rather by the prospects of fluidity that allow the already hybridised culinary culture to develop.